The regulation of the legal entity name in Article 151 of the CCCN . Analysis of requirements and problems of interpretation and application (Nueva Epoca, 2020)
The entry into force of the Civil and Commercial Code has introduced through Article 151 requirements for the recognition and prote ction of the name of legal entities that is generating many problems of interpretation and application. In this paper we analyze the regulation highlighting the problems it generates and the arguments why we believe its revision is necessary
Keywords: Name; Corporate name; Trademarks; Legal entities